Privatizing Latin American Garbage? It’s complicated: A View from the Northern Border of Latin America - Hill, Sarah (2015)
In the early 1970s, a plucky group of 200 pepenadores (scavengers) in Ciudad Juárez, Mexico, secured a 25-year concession to recover recyclable materials deposited in that city’s dump, along with the right of first refusal on a second 25 year contract. And so began a celebrated chapter in the long saga of Socosema, one of Mexico’s most—for a time— successful worker owned recycling cooperatives. And, as well, so marked another chapter in a long-standing tension in Mexico between “public” and “private” management of waste.